Evaluasi Penerapan Saat Pengakuan Pendapatan terhadap Kelayakan Laba secara Periodik (Studi Kasus pada Perusahaan Konstruksi) - Joni . (Jurnal Akuntansi, 2005)
The Purpose of this study is to evaluate the proper timing ofrevenue recognition and the measurement of revenue to get fair value of periodic earnings for construction enterprise. This study use descriptive analysis method The purpose of this method is to describe and analyze data, in order to give a comprehensive information of the object. The result of this study indicated that the proper timing of revenue recognition for construction enterprise is during the production process with percentage-of-completion methodKey Word: revenue recognition, revenue measurement, periodic earnings